Content Language Integrated Learning (CLIL) Design in Indonesian Language Learning Oriented to Pancasila Student Profiles to Build Global Diversity - Rijadi, Arief; Parto, Parto; Mutiah, Arju; Syukron, Ahmad (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
Indonesian Language is a subject that has a wide reach and in the last 2 years, since 2021, the Ministry of Education and Culture has ordered each educational unit to build the character of Pancasila Student Profiles. This research is qualitative research with an evaluative descriptive design. The research stages begin with preparing a research proposal and research instruments, data collection, data reduction, data analysis, data conclusion, and report preparation. The theory used is CLIL, namely thematic-integrative terms in the 2013 Curriculum as an embodiment of CLIL implementation. Coyle (2007) proposed 4C as an application of CLIL, namely content, communication, cognition, culture (community/citizenship). The research results show that in implementing Pancasila student profiles, it is important to prioritize a holistic, integrated and contextual approach. The aim is not only for students to have a theoretical understanding of Pancasila, but also to be able to apply these values in real life by becoming responsible, tolerant citizens and contributing positively to society. Moreover, the implementation of global diversity in learning can help students become global citizens being aware of differences and have the ability to interact positively in an increasingly connected and diverse society.